Pelatihan Computational Thinking Sebagai Metode Problem Solving Kepada Guru SMP di Kabupaten Luwu Utara - Muhammad Riska Babo; Hilda Ashari; Elfira Makmur (Jurusan Teknik Informatika dan Komputer, 2023)
Improving problem-solving skills is crucial in facing global competition. Therefore, it is important to provide early training. With the development of technology and computer usage, a new approach has emerged in developing problem-solving skills known as Computational Thinking (CT). CT is based on the fundamental principles of computer science, where problems are understood in abstract terms and solutions are developed through illustrations. Since 2016, Indonesia has actively participated in the Bebras Community and promoted Computational Thinking through the organization of Bebras Challenge for students nationwide. The Faculty of Engineering at UNM has also been involved as a Bebras Bureau in organizing the Bebras Challenge in South Sulawesi. The Bebras training for teachers aims to introduce Computational Thinking skills so that every teacher can teach and train their students in developing problem-solving skills. The training was attended by representatives from 100 junior high schools in North Luwu Regency.Kabupaten Luwu Utara.